Is it all about race? Intergroup threat and perceptions of racial profiling - Thomas, Shaun A. (Criminal justice studies, 2017)
Relatively few studies have assessed theoretically relevant predictors of individual’s perceptions of racial profiling by law enforcement officers. The current study addresses this limitation by drawing on theoretical frameworks highlighted in the growing body of literature examining disproportionate minority contact (DMC) with the criminal justice system. Specifically, we draw on the racial and symbolic threat perspectives with the objective of identifying theoretically relevant individual and community level predictors of perceptions of racial profiling by public and private police bodies in airports, malls, and on the roads. Results of our analysis of data on White and Black individuals nested within communities support the racial threat perspective in documenting the influence of racial heterogeneity and interracial labor market competition on perceptions of racial profiling. However, in contention to predictions derived from the symbolic threat perspective, the results fail to uncover a link between interracial socioeconomic inequality and perceptions of racial profiling by law enforcement officers. These results highlight the importance of moving beyond individual explanations of profiling and other forms of DMC and suggest community characteristics and perceptions of intergroup threat are particularly salient to understanding perceptions of race-based distinctions in formal social control.